Correlation of pap smear and colposcopic finding of cervix with histopatholgiocal report in a group of patient attending in a tertiary hospital - Parvin, Suraiya; Kabir, Nazneen; Lipe, Yeasmin Samad; Nasreen, Khaleda; Alam, KM Nurul (Journal of Dhaka Medical College, 2013)
Objective: To correlate Paps smear and colposcopic finding of cervix with histopathological report of abnormal area of cervix in a group of patient attending a tertiary hospital. Methods: It was a cross-sectional prospective study done in one year period from January to December 2007 in Colposcopy Clinic of Institute of Child and Maternal Health (ICMH) Hospital, Dhaka. The study carried out including fifty two female patients having clinically unhealthy cervices as in the form of hypertrophy, erosion, congestion or bleeds on touch or having positive pap smear found during P/V or P/S examination, attending gynaecology out patient department of ICMH Hospital after fulfilling all the inclusion criteria. Result: The present study showed a correlation between cervical cytology and colposcopically directed biopsy, the correlation was accurate within one grade in 39 of 51 cases (76.16%) (as cytology was not done in one case). Other studies showed cytologic accuracy (within one level of histologic finding) to about 83% and 88% cases. Conclusion: The study done here shows excellent correlation between findings of colposcopy with that of histopathology of guided biopsy. It also confirms the diagnostic value of colposcopy in the management of women with abnormal cervical cytology with squamous atypia. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15604 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 39-44